DEVELOPMENT OF SOCIAL FORESTRY GOVERNANCE RESEARCH FOR SUSTAINABLE FOREST MANAGEMENT: BIBLIOMETRIC ANALYSIS - Shinta Iryaningsih; Sambas Basuni; Hartrisari Hardjomidjojo (RADJA PUBLIKA, 2026)
Research on social forestry governance in supporting sustainable forest management continues to grow along with increasing attention to the issues of deforestation, climate change, and empowerment of forest communities. However, this research development is still scattered across various themes, so an analysis is needed to map the structure of knowledge and the direction of the study's development comprehensively. This study aims to analyze publication trends, dominant themes, and the conceptual structure of research related to social forestry governance using a bibliometric approach. Research data was obtained from the Scopus database with a publication range of 2014–2024 using the keywords social forestry, community forestry, forest governance, and sustainable forest management. A total of 294 publications were analyzed using Bibliometrix, Biblioshiny, and VOSviewer software through co-occurrence analysis, thematic maps, and Multiple Correspondence Analysis (MCA). The results show that the trend of scientific publications has experienced a significant increase, especially after 2018. Dominant themes in the research include forest management, community forestry, forest governance, sustainability, ecosystem services, and conservation. The analysis also shows that social forestry research is developing in a multidisciplinary manner, focusing on collaborative governance, community participation, environmental sustainability, and institutional strengthening in forest management. Thus, social forestry governance plays a crucial role in supporting sustainable forest management through the integration of social, economic, and ecological aspects.